2004
DOI: 10.1002/jmv.20255
|View full text |Cite
|
Sign up to set email alerts
|

An interferon‐γ‐related cytokine storm in SARS patients

Abstract: Fourteen cytokines or chemokines were analyzed on 88 RT-PCR-confirmed severe acute respiratory syndrome (SARS) patients. IFN-gamma, IL-18, TGF-beta, IL-6, IP-10, MCP-1, MIG, and IL-8, but not of TNF-alpha, IL-2, IL-4, IL-10, IL-13, or TNFRI, were highly elevated in the acute phase sera of Taiwan SARS patients. IFN-gamma was significantly higher in the Ab(+) group than in the Ab(-) group. IFN-gamma, IL-18, MCP-1, MIG, and IP-10 were already elevated at early days post fever onset. Furthermore, levels of IL-18, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
654
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(707 citation statements)
references
References 27 publications
36
654
0
17
Order By: Relevance
“…Recent analysis indicates that the proinflammatory cytokine storm is a major contributor to lung injury and death during respiratory viral infection, and IFN-␥, as a member of the cytokine storm, plays a critical role in this process (15). In our study, the levels of IFN-␥ in BALF were increased and reached a peak at day 3 after RSV infection (Fig.…”
Section: Rsv Infection Induces Acute Lung Immune Injury In Micesupporting
confidence: 60%
“…Recent analysis indicates that the proinflammatory cytokine storm is a major contributor to lung injury and death during respiratory viral infection, and IFN-␥, as a member of the cytokine storm, plays a critical role in this process (15). In our study, the levels of IFN-␥ in BALF were increased and reached a peak at day 3 after RSV infection (Fig.…”
Section: Rsv Infection Induces Acute Lung Immune Injury In Micesupporting
confidence: 60%
“…For instance, higher levels of proinflammatory mediators are seen in people with fatal hemorrhagic YFV infections compared with people experiencing less severe infections (15). Indeed, a more exuberant early immune response is often associated with more severe disease following zoonotic infections, such as SARS coronavirus, dengue virus, hantavirus, chikungunya virus, and the 1918 influenza A virus strain (73)(74)(75)(76)(77). The precise mediators of immunopathologic responses seen in nonnatural hosts following zoonotic viral infections may differ in different hosts and different infections, and many cytokine pathways (e.g., type I IFN) may well play both beneficial and detrimental roles in the host response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that both the types of infected cells and related cytokines could be associated with pathogenesis of ECF. Recently, it has been reported that the cytokine storms in humans are strongly associated with high mortality and increased severity of disease in several fatal infections such as malaria [8], severe acute respiratory syndrome [12], Ebola virus infection [2] and highly pathogenic avian influenza [26]. Among these diseases, main causative cytokines for the cytokine storm seem to be pro-inflammatory cytokines such as IL-1β IL-6 and TNF-α.…”
Section: Discussionmentioning
confidence: 99%